1995
DOI: 10.1073/pnas.92.5.1262
|View full text |Cite
|
Sign up to set email alerts
|

Transport of proteins dissolved in organic solvents across biomimetic membranes.

Abstract: Using lipid-impregnated porous cellulose membranes as biomimetic barriers, we tested the hypothesis that to afford effective transmembrane transfer of proteins and nucleic acids, the vehicle solvent should be able to dissolve both the biopolymers and the lipids. While the majority of solvents dissolve one or the other, ethanol and methanol were found to dissolve both, especially if the protein had been lyophilized from an aqueous solution of a pH remote from the protein's isoelectric point. A number of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Although enzymes do not have to be dissolved in organic solvents to work as catalysts (and indeed they usually are not) (Koskinen and Klibanov, 1996), in order to explore protein folding in nonaqueous media the latter should dissolve both folded and unfolded proteins. Fortunately, over the last several years it has been found that, under optimal conditions, proteins are indeed highly soluble in more than a dozen neat organic solvents (Bromberg and Klibanov, 1995;Chin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although enzymes do not have to be dissolved in organic solvents to work as catalysts (and indeed they usually are not) (Koskinen and Klibanov, 1996), in order to explore protein folding in nonaqueous media the latter should dissolve both folded and unfolded proteins. Fortunately, over the last several years it has been found that, under optimal conditions, proteins are indeed highly soluble in more than a dozen neat organic solvents (Bromberg and Klibanov, 1995;Chin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The insulin remained in its native conformation with increased thermal stability (T m ), when compared with water Manning et al, 1995). Insulin (pH 3.0) solubility in EtOH increased from 14 mg/ml to 830 mg/ml with the addition of SDS (Bromberg and Klibanov, 1995). Similar results were obtained with α-chymotrypsin in sodium bis(2-ethylhexyl) sulfosuccinate (Manning et al, 1995).…”
Section: Referencesupporting
confidence: 83%
“…MeOH >10 (Chin et al, 1994) TFE >10 (Chin et al, 1994) Ethylene glycol >10 (Chin et al, 1994) DMSO >100 (Houen, 1996) Glycerol >100 (Houen, 1996) Myoglobin Ethanol 0.59 (Bromberg and Klibanov, 1995) Methanol >5 (Bromberg and Klibanov, 1995) Salmon Calcitonin 70% EtOH 50 (Stevenson and Tan, 2000) 70% DMSO 50 (Stevenson and Tan, 2000) Water 100 (Stevenson and Tan, 2000) Ribonuclease Ethanol <0.005 (Bromberg and Klibanov, 1995) Methanol 0.61 (Bromberg and Klibanov, 1995) Table 3. Solubility of proteins in co-solvent and non-aqueous conditions.…”
Section: Referencementioning
confidence: 98%
See 2 more Smart Citations